2019
DOI: 10.1039/c9nr07116d
|View full text |Cite
|
Sign up to set email alerts
|

Nanocellulose/graphene oxide layered membranes: elucidating their behaviour during filtration of water and metal ions in real time

Abstract: In situ SAXS and reactive molecular dynamics (ReaxFF) computational simulations of water and metal ion interaction with CNF–GO layered membranes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 39 publications
(41 reference statements)
0
27
0
Order By: Relevance
“…[9][10][11][12] In the case of graphene oxide, which is a rather economical (though non-conductive) alternative of graphene, a major problem as nanoller is the lack of interfacial bonding with the polymer matrix (due to its high hydrophilicity), therefore leading to poor dispersion and agglomeration of the nanosheets. [13][14][15] Nevertheless, GO has a vast amount of reactive functional groups, such as hydroxyl, epoxy, and carbonyl groups, [16][17][18][19][20] which provide reactive sites for surface modifying the nanosheets to tailor specic properties, such as enhancing their compatibility with polymer matrices. 15,21 Even though different surface modication techniques in GO have been previously explored, [22][23][24][25] in this work we take advantage of the high reactivity of alkylamines to modify the surface of GO.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12] In the case of graphene oxide, which is a rather economical (though non-conductive) alternative of graphene, a major problem as nanoller is the lack of interfacial bonding with the polymer matrix (due to its high hydrophilicity), therefore leading to poor dispersion and agglomeration of the nanosheets. [13][14][15] Nevertheless, GO has a vast amount of reactive functional groups, such as hydroxyl, epoxy, and carbonyl groups, [16][17][18][19][20] which provide reactive sites for surface modifying the nanosheets to tailor specic properties, such as enhancing their compatibility with polymer matrices. 15,21 Even though different surface modication techniques in GO have been previously explored, [22][23][24][25] in this work we take advantage of the high reactivity of alkylamines to modify the surface of GO.…”
Section: Introductionmentioning
confidence: 99%
“…The molecular dynamics simulations data confirm the motion of the metal (Cu 2+ and Ag + ) ions into the membrane for the formation of metal clusters during adsorption (Figure 5) (Zhu et al, 2018). The high adsorption performance of the prepared membrane is mainly due to the synergistic effect of GO and CNFs (Valencia et al, 2019). GO/carboxymethyl cellulose nanofibril (CMCNF)-Fe 3+ exhibited high adsorption efficiency for Pb 2+ with good adsorbent recovery (Yu et al, 2020).…”
Section: Nanocellulose Hybrids Adsorbent For Metal Ionsmentioning
confidence: 60%
“…; for e.g., hybrid materials that show high mechanical properties and offer high adsorption capacities (Table 2). Nanocellulose-graphene oxide (GO) membranes were reported for the adsorption of metal ions (Cu 2+ and Ag + ) from aqueous solutions (Zhu et al, 2017(Zhu et al, , 2018Valencia et al, 2019). The adsorption process was followed in real-time using insitu small-angle X-ray scattering (SAXS) and reactive molecular dynamics (ReaxFF) computational simulations (Figure 5).…”
Section: Nanocellulose Hybrids Adsorbent For Metal Ionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The high rejection rate, structural stability, high flux, and easy preparatory method makes the GO‐CNF membranes a worthy contender for membranes currently adopted for water remediation, food industry, and biomedicine. [ 112 ] From the tests conducted by Valencia et al, [ 113 ] the results showed that the enhanced wet mechanical properties arose from the prevention of expansion of the CNF network during water filtration due to the incorporation of a GO layer, which also appeared to protect the cellulose network from variations in the structure during re‐drying hence preventing dramatic collapse as occurs in a pristine CNF membrane.…”
Section: Nanocellulose Based Membranesmentioning
confidence: 99%